A case report of primary myxoid liposarcoma mimicking as a parotid cystic lesion. Issue 2 (14th January 2022) - Hong, Yong Tae; Yang, Yunna; Lee, Hyunjun
Abstract: Rationale: Myxoid liposarcoma (MLS) is an extremely rare tumor of the salivary gland and it arises from undifferentiated pluripotent mesenchymal cells. We report a rare case of a primary MLS in the parotid gland. Patient concerns: The patient was a 49-year-old female who presented with a hard fixed mass in the left parotid region. Diagnosis: On computed tomography and MR images, this tumor has a low attenuation center with a thick enhancing wall and ill-defined margins. The absence of high-signal-intensity foci on T1-weighted images makes a MLS indistinguishable from most other soft-tissue masses. Pathologically, the tumor was diagnosed as MLS. Interventions: The patient received total parotidectomy with facial nerve preservation and selective neck dissection. Outcomes: Immediate facial nerve function was House Brackmann Grade III and recovered within 3 months after the surgery. Follow-up period is 57 months and there was no recurrence until now. Lessons: In this report, we report a rare case of primary MLS mimicking a cystic lesion of the parotid gland.